Esophageal atresia in a premature - Cabrera de Aguirre, María T; Birenbaum, Manuel; Fonseca, Daniel; Martell, Miguel; Quian, Jorge; Capurro, Haroldo; Peña, José L; Lieutier, Gastón (Cirugía del Uruguay, 1974)
a) A premature infant, born after 34 weeks of gestation and weighing at birth 1900 grms. and at the time of operation 1 600 grms., presented esophageal atresia. b) Surgery was performed 36 hours after birth. c) There is pre- and post-operatory alteration of respiratory rhythm and apneic pauses due to the infant's prematurity. d) For the infant's survival strict pediatric, anaesthetic, nursing and environmental care are required. e) In arder to preserve .he Jife of high-risk premature infants i t is essential to · have specialized Centres.